2006
DOI: 10.1007/s00508-006-0661-7
|View full text |Cite
|
Sign up to set email alerts
|

Kokainmissbrauch in Wien und in europäischen Metropolen – eine multizentrische Studie

Abstract: The European trend of increased cocaine use could also be observed in Vienna. One of the greatest barriers for establishing adequate treatment settings for this target group is the difficulty to reach this population. In addition, multiple substance abuse seems to be one of the predominating patterns of cocaine consumption and this aspect should be integrated within treatment (in the treatment and scene groups additional heroin and benzodiapzepines abuse is observed, in the party group intensive alcohol consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…According to the Office of Applied Studies, Substance Abuse and Mental Health Services Administration (SAMHSA) in the USA [1], heroin is among the three most frequently reported drugs that result in emergency department visits, and there are similar results from studies conducted in Europe [10]. Reports in the 1990s indicated that inhalation as a means of substance abuse had increased among primary heroin admissions.…”
Section: Discussionmentioning
confidence: 77%
“…According to the Office of Applied Studies, Substance Abuse and Mental Health Services Administration (SAMHSA) in the USA [1], heroin is among the three most frequently reported drugs that result in emergency department visits, and there are similar results from studies conducted in Europe [10]. Reports in the 1990s indicated that inhalation as a means of substance abuse had increased among primary heroin admissions.…”
Section: Discussionmentioning
confidence: 77%
“…A variety of research findings support the easier availability of illicit substances in urban areas, particularly the availability of cocaine is known to be increased [20,21,22]. These differences in cocaine availability have also been shown for European city comparisons, and were confirmed in a multi-site investigation of cocaine consumption patterns in capital cities of the EU, with a significantly lower prevalence for Vienna, which was not comparable to larger US cities [23]. …”
Section: Discussionmentioning
confidence: 87%
“…Das Crackrauchen ist aber nicht in allen europäischen Ländern verbreitet; wie die Arbeit von Bäwert et al in dieser Ausgabe der Wiener klinischen Wochenschrift zeigt, gibt es z.B. in Wien nur wenige Crackraucher [8]. Ein wichtiges Konsummuster bei denjenigen Kokainkonsumenten, die opiatabhängig sind und weiterhin Heroin intravenös konsumieren, ist die kombinierte Einnahme von Heroin und Kokain in einer Spritze, welches auch "speedball" genannt wird, verbreitet [9].…”
Section: Kokainkonsum: Die Therapeutische Herausforderung Durch Diverunclassified
“…Kokain wird nur selten als alleinige Substanz konsumiert -fast alle konsumieren zusätzlich eine andere psychoaktive Substanz [7,8] [12,13]. Bei Opiatabhängigen in einer Substitutionsbehandlung wird angenommen, dass Kokain eingesetzt wird, um die sedierende Wirkung des Methadons zu entgegnen.…”
Section: Kokainkonsum: Die Therapeutische Herausforderung Durch Diverunclassified